Efeitos do processo de formação de docentes. Perspectiva multinível-multidemensional - Blancas Torres, Evelin Ketty (2021)
Multilevel-multidimensional development receives special attention in the teacher training process. The research seeks to determine the effects of the training process on the development of the levels of consciousness and human dimensions of the students of the Faculty of Education. Being as a study unit 149 students evaluated at the end of their training process. It was done using an intuitive-inductive method, collecting information through in-depth observation techniques and a semi-structured interview. The results indicate that training with an integral vision has significant effects and traditional mechanistic training does not contribute to the multilevel-multidimensional development of students.